(untitled) (World Bulletin of Public Health, 2024)
Among oncological diseases, breast cancer (BC) in women occupies a leading place throughout the world. There have been advances in its treatment, but early diagnosis of breast cancer is limited by the capabilities of X-ray mammography and ultrasound and therefore often requires additional methods for examining the mammary glands